Analisa Pola Keruntuhan Konstruksi Rangka Atap dengan Menggunakan Profil Baja Ringan - Andry Sucipta; Anis Saggaff; Sutanto Muliawan (Jurnal Teknik Sipil dan Lingkungan, 2013)
Truss light steel is a modern technology of roof truss made of a thin plate of zinc-alum which is designed by computers and manufactured by machines. Truss light steel can be an alternative choice to support the roof to be able to deal with the extreme weather conditions, not to be distracted from termite attack and to be held longer than truss form wood. From its material, there are some weaknesses of light steel, among other are buckling and deflection occurs, so that a review was made of the failure that will occur in some spans and truss forms.Â  SolidWorks is a Computer Aided Design (CAD) 3D program using the Windows operating system. SolidWorks program can provide the simulation and compute the forces that arise in structures which designed by using finite element method. The use of SolidWorks program shows the simulation of failure mode that will occur, so it can be the input for the planning and construction of the better light steel. This analysis used the truss of type pratt and howe with theoretical spans 12 m and 24 m at 300 angle. The components used were profile lip channel 75x32.8x7.95 and tek screw formed in SolidWorks program. The results obtained in the SolidWorks program was the failure occurred because of flexural buckling in A6 rod to the entire spans and forms. Truss pratt type was stronger to resist the loads on the theoretical span of 12 m and theÂ  howe type was stronger to resist the loads on the theoretical span 24 m. Diagonal mounting differences affected the strength of each spans. Key Words: truss, light steel, SolidWorks, failure mode